The use of English epistemic modality among ESL learners - Subra Govindasamy (Journal of Modern Languages)
The acquisition of expressions of epistemic modality or the probability system seems to be a problem to second language leamers of English. While expressing basic propositions is not too difficult, second language leamers of English appear to have trouble in suggesting or giving personal opinions as to the expected probability of an event. This is not to be totally unexpected since even very advanced learners of English send mixed signals by using inappropriate modals (Altman, 1982).